SINTESIS KARBOKSIMETIL KITOSAN TERHADAP PENGARUH KONSENTRASI NATRIUM HIDROKSIA DAN RASIO KITOSAN DENGAN ASAM MONOKLORO ASETAT - Rahmawati, Helda; Iskandar, Dodi (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2014)
This study aims to determine the effect of NaOH concentration and the ratio of monocloro acetic acid with chitosan used in the synthesis process to the degree of substitution and solubility in water. Preparation of carboxymethyl chitosan (CMCts) was carried out by various concentration of NaOH and ratio of monochloro acetic acid with chitosan. The concentration of NaOH used in the alkalination process were 10, 20, 30, 40, and 50% (w/v). The ratio of chitosan: monochloro acetic acid used for etherification were 1:0,5; 1:1; 1:1,5; and 1:2 (w/w). Etherification was carried out at a temperature of 60Â°C for 2 hours. The results showed that the NaOH concentration of 10-30% (w/v) increased the substitution degree and solubility of produced CMCts. But at concentrations above 30% (w/v) the substitution degree and solubility were decreased. The ratio of chitosan : monochloro acetic acid also affect to substitution degree and the solubility of synthesized CMCts. The higher amount of monochloro acetic acid added to chitosan, the higher is substitution degree and the solubility of carboxymethyl chitosan synthesized in water. The best result was obtained when the ratio of chitosan : monochloro acetic acid were 1:2 (w/w). Within this ratio a 92.05% of yield was resulted with a solubility of 28.05 g/L and a substitution degree of 0.72.